Fundamentals of Digital Circuits - Kumar, A. Anand, author 389796 (New Delhi : PHI Learning, 2009)
It is designed for use by the undergraduate students pursuing courses in areas of engineering disci-plines such as Electrical and Electronics, Electronics and Communication, Electronics and Instrumentation, Telecommunications, Medical Electronics, Computer Science and Engineering, and Information Technology. It is also useful as a text for MCA, M.Sc. (Electronics) and M.Sc. (Computer Science) students. Appropriate for self study, the book is useful even for AMIE and IETE students. Written in a student-friendly style, the book provides an excellent intro-duction to digital concepts and basic design techniques of digital circuits. It discusses Boolean algebra concepts and their application to digital circuitry, and elaborates on both combinational and sequential circuits. The book provides numerous fully worked out, laboratory tested examples to give students a solid grounding in the related design concepts. It includes a number of review questions and classroom tested problems at the end of each chapter. As the book requires only an elementary knowledge of electronics to understand most of the topics, it can also serve as a textbook for students of polytechnics, B.Sc. (Electronics) and B.Sc. (Computer Science).